Structures for biomimetic, fluidic, and biological applications - Stratakis, Emmanuel; Jeon, Hojeong; Koo, Sangmo (Materials Research Society, 2016)
Controlling the interactions of light with matter is crucial for the success and scalability of materials-processing applications. When ultrashort pulsed lasers are used, the optimal interplay between the laser and the material parameters enable highly precise and controllable fabrication, allowing structuring down to the nanometer scale. Besides this, a unique aspect for many applications is the possibility of material modifications at multiple length scales, leading to complex micro- and nanoscale architectures, while adding a new dimension to optimization of the structures. As a result, femtosecond laser micro-/nanoprocessing offers unique capabilities for three-dimensional, material-independent modification, opening new opportunities for innovation and exploitation in the materials industry. This article focuses on the implementation of ultrashort pulsed laser-based micro- and nanofabrication methodologies for the realization of structures relevant to biomimetic, fluidic, and biological applications. The wealth of possibilities and the number of new approaches for obtaining complex high-resolution features at the micro- and nanoscales are demonstrated.